2017
DOI: 10.1111/bju.13989
|View full text |Cite
|
Sign up to set email alerts
|

Female urethral injuries associated with pelvic fracture: a systematic review of the literature

Abstract: To review systematically the literature on female urethral injuries associated with pelvic fracture and to determine the optimum management of this rare injury. Using Meta-analysis of Observational Studies in Epidemiology criteria, we searched the Cochrane, Pubmed and OVID databases for all articles available before 30 June 2016 using the terms 'female pelvic fracture urethroplasty', 'female urethral distraction', 'female pelvic fracture urethral injury' and 'female pelvic fracture urethra girls.' Two authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…As for children, the skeletally immature pelvis is more plastic and flexible because there is a more percentage of cartilage, a more porous cortical bone, and the pubic symphysis and sacroiliac joints are more elastic [ 1 ], hence the pelvic absorbs higher energy during trauma. Also, girl’s bladder neck and urethra are more vulnerable because the relative higher position in the pelvis [ 2 ], which may explain why the proportion of girls urethral injuries is higher than female adults in the current literature [ 3 ]. Although rare, the management of female pelvic fracture urethral injuries is complex and there is no guideline yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for children, the skeletally immature pelvis is more plastic and flexible because there is a more percentage of cartilage, a more porous cortical bone, and the pubic symphysis and sacroiliac joints are more elastic [ 1 ], hence the pelvic absorbs higher energy during trauma. Also, girl’s bladder neck and urethra are more vulnerable because the relative higher position in the pelvis [ 2 ], which may explain why the proportion of girls urethral injuries is higher than female adults in the current literature [ 3 ]. Although rare, the management of female pelvic fracture urethral injuries is complex and there is no guideline yet.…”
Section: Discussionmentioning
confidence: 99%
“…Black et al [ 4 ] indicated that the bladder neck injury should be repaired primarily because it is crucial in continence. Patel et al [ 3 ] did a systematically review of the literature about female urethral injuries associated with pelvic fracture, their results showed that patients who had primary alignment were more likely to have urethral stenosis and fistula. From our perspective, patients who had extensive urethra injury often accomplished by serious damage of other organs, the principle is to deal with life-threatening risks first, so the patients were mostly managed with suprapubic cystotomy and deferred repair [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Function recovery is important in patients with vaginal injury for the high incidence of vaginal stenosis and sexual dysfunction. [6,10,13,21] Harvey-Kelly KF [22] reported that rate of sexual dysfunction after pelvic fracture could be as high as 40%. Heather's study showed 25.7% female pelvic fracture patients reported pain in intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal laceration after pelvic trauma is rare with incidence about 2% to 4% in previous reports [6][7][8][9]. The reduced bleeding because of the contraction of vaginal smooth muscles as a posttraumatic stress reaction and the severe injuries of other organs associated with pelvic fracture may result in missed diagnosis of vaginal injury and potentially lead to various complications including pelvic infection, vaginal stenosis and sexual dysfunction [6,10]. It might be considered as an underestimated issue in the care of high energy blunt pelvic trauma in female patients.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal laceration after pelvic trauma is rare with an incidence about 2 to 4% in previous reports [69]. The reduced bleeding because of the contraction of vaginal smooth muscles which acts as a post-traumatic stress reaction and the severe injuries of other organs associated with pelvic fracture may result in missed diagnosis of vaginal injury and potentially lead to various complications including pelvic infection, vaginal stenosis and sexual dysfunction [6, 10]. It might be considered as an underestimated issue in the care of high energy blunt pelvic trauma in female patients.…”
Section: Introductionmentioning
confidence: 99%